The role of marketing stimuli and attitude in determining post-COVID buying decisions toward organic food products: evidence from retail consumers in Beijing, China - Jiang, Yuling; Abdullah, Siti Intan Nurdiana Wong; Lim, Bernard Heng Jit; Wang, Ruiyun; Phuah, Kit Teng (Frontiers in Sustainable Food Systems, 2023)
Customers are diverse, and their preferences have changed tremendously especially post pandemic and many business organizations are facing major challenges in meeting those needs. Therefore, in-depth understanding of consumer buying decision plays a vital role to develop effective strategies. The aim of this study is to determine whether the marketing mix (4Ps) elements and their attitude have a significant effect towards organic food products buying decision among retail consumers in Beijing, China. A quantitative method was used in this study, whereby 334 questionnaires were physically collected randomly from walk-in customers at Walmart, Darunfa, and Yonghui supermarket in Beijing, China. Based on the results of hypothesis testing using PLS-SEM, it confirms that all 4Ps have a significant positive relationship with consumer buying decision and attitude played a mediator role while income had no moderating effect. Results of this study provided relevant suggestions to marketing practitioners especially organic food producers and retail stores on developing and implementing marketing strategies effectively.